Paare und Ungleichheit(en) Eine Verhältnisbestimmung - Rusconi, Alessandra; Wimbauer, Christine; Motakef, Mona; Kortendiek, Beate; Berger, Peter A. (GENDER Sonderheft, 2013)
The authors of the second GENDER special issue examine couple relationships as a central place where gender inequalities are (re) produced, compensated for or reduced. In the sense of a 'doing couple', 'doing gender' and 'doing (in) equality', the requirements of gainful employment, the socio-political framework and negotiation processes of the couples play an important role.